FACTOR OF IDENTITY IN THE PROCESS OF FORMATION OF THE LATIN AMERICAN REGION - Iryna Pidkurkova (Вісник НЮУ імені Ярослава Мудрого: Серія: Філософія, філософія права, політологія, соціологія, 2022)
The article considers the evolution of the concept of “region”, which in the modern sense is no longer just a geographical entity. Prerequisites for its formation in a given area are historical, socio-cultural features, as well as the specifics of political organization. It is noted that in the process of regionalism (integration processes associated with the acquisition of subjectivity by regions), the actors of international relations form a certain degree of regional ability to articulate their interests. Based on the ideas of A. Harrell and A. Paasi on the formation of regions, the role of regional identity in this process is determined. The factors of identity of South American countries and the role of regional identity in the process of formation of the Latin American macroregion is considered. It is concluded that in the international arena, Latin American states are increasingly acting as an ideologically integrated entity due to the factor of identity and the formation of a common Latin American consciousness.